(untitled) (Research, Society and Development, 2022)
Seeds with high vigor result in better plant establishment and can therefore improve the use of nutrients, especially phosphorus (P). Thus, the objective was to evaluate the growth and P absorption by the common bean as a function of seed vigor in soils with contracting textures. The treatments were set up in a 2x5 factorial scheme, combining high and low seed vigor with five doses of P that were 0, 35, 70, 140 and 280 mg dm-3 in medium texture soil and 0, 50, 100, 200, 400 mg dm-3 in clayey soil. Four plants of the cultivar Dama were grown in pots containing 5 dm-3 of soil and evaluated until flowering began. High vigor seeds resulted in an increase in plant dry matter (shoot + root) of 11 and 15% in medium textured and clayey soils, respectively. Photosynthesis increased in plants originating from high vigor seeds by 26.04% in medium textured soil, but it was similar between high and low vigor seed plants in clayey soil. The dose of P necessary to reach at least 95% of maximum photosynthesis was 46% higher in plants originated from seeds with low vigor. The accumulation of P in plants of high vigor seeds cultivated in medium-textured soil was 37% greater than that of low vigor seeds. In clayey soil there was no such difference, however, the dose of P in the soil to reach the maximum accumulation was lower when the seeds were of high vigor. The P recovery rate was higher in plants originated from seeds with high vigor in both soils. It is concluded that plants from seeds with high vigor present greater growth and accumulation of P, which highlights the importance of using seeds with high vigor for a better use of phosphate fertilizers in common bean.